Antibacterial Activity Test of Sungkai Leaf Endophytes (Peronema canescens J) Against Escherichia coli and Staphylococcus aureus Bacteria as Antidiarrheal Probiotic Candidates - Septa Pratama; Violin Carrissa; Nazmi Rajali Siregar (Integrated Science Education Journal, 2026)
Purpose of the study: This study aims to test the antibacterial activity of endophytic bacterial isolates from sungkai leaves against the two test bacteria as antidiarrheal probiotic candidates. Methodology: The research stages included isolation, morphological characterization, Gram staining, motility testing, catalase testing, and antibacterial activity testing using the well diffusion method. Data were analyzed using Shapiro-Wilk, ANOVA, and Tukey's advanced test. Main Findings: The results of the study obtained five isolates (S-1, S-2, S-3, S-4, S-5) with Gram-positive characteristics, bacilli, and positive in motility and catalase tests. Isolates S-1 and S-2 did not have antibacterial activity. In contrast, isolates S-3, S-4, and S-5 were able to inhibit the test bacteria with moderate to strong categories. The highest activity against Escherichia coli was shown by isolate S-3 (10.3 mm), while against Staphylococcus aureus by isolate S-4 (12.08 mm). Statistical analysis showed a significant difference in antibacterial activity between treatments (p<0.001). It was concluded that isolates S-3 and S-4 have the most potential to be developed as antidiarrheal probiotic candidates and natural antibacterial sources. Novelty/Originality of this study: The originality of this study lies in integrating endophytic bacterial exploration from Peronema canescens leaves with antibacterial screening against Escherichia coli and Staphylococcus aureus to identify potential probiotic candidates for antidiarrheal applications.